Implementing AI Chatbots in Customer Service Optimization—A Case Study in Micro-Enterprise - Marcineková, Katarína; Janáková Sujová, Andrea; Ďurica, Rastislav (MDPI AG (Multidisciplinary Digital Publishing Institute-MDPI), 2025)
Digitalization, including the implementation of artificial intelligence (AI) applications, is one of the key enablers of business agility in contemporary enterprises. Micro and small enterprises (MSEs) are increasingly expected to adopt scalable and cost-effective AI tools as part of their digital transformation. This study investigates the implementation of an AI-powered chatbot in a Slovak micro-enterprise operating an e-commerce platform, aiming to assess its effectiveness in automating customer service processes. Using a mixed-method case study approach, the research combines quantitative data on service performance (e.g., number of inquiries handled, response time, and automation rate) with qualitative insights from employee and customer feedback. The findings show that the chatbot significantly reduced staff workload and improved response speed and customer satisfaction. However, challenges were identified in handling ambiguous queries and maintaining empathetic communication in complex situations, underscoring the need for regular updates and human oversight. The study contributes to the limited empirical literature on AI integration in micro-enterprises and provides practical recommendations for MSEs seeking to enhance their operational efficiency through AI-driven tools without large-scale investments. These results offer a nuanced perspective on how even resource-constrained businesses can benefit from AI adoption when implementation is carefully aligned with their specific needs and capabilities.
Keywords: artificial intelligence; chatbot; customer service automation; micro-enterprise; agility enabler; digital transformation; affordable AI tools; case study; e-commerce